Gallbladder mucosal lesions associated with high biliary amylase irrespective of pancreaticobiliary maljunction. Issue 6 (7th August 2017) - Free, Jason; Wang, Frank; Williams, Nick; Gundara, Justin S.; Staerkle, Ralph F.; Hugh, Thomas J.; Samra, Jaswinder S.
Abstract : Background: Previous studies have focused on the presence of reflux in selected cohorts with pancreaticobiliary maljunction (PBM), but little is known regarding the wider incidence of occult reflux and associated mucosal changes. We aimed to correlate gallbladder mucosal abnormalities with objective evidence of PBM and occult pancreaticobiliary reflux (PBR) in an Australian population undergoing cholecystectomy. Methods: Patients undergoing cholecystectomy between September 2010 and September 2012 were eligible for inclusion. Demographic and pre‐operative clinical data were collated and entered into a pre‐defined database. Operative cholangiograms were routinely performed and the presence of PBM noted. Gallbladder bile samples were analysed for bilirubin (<20 µmol/L), amylase (<100 U/L) and lipase (<70 U/L) levels. Evidence of PBR was correlated with gallbladder mucosal findings. Results: A total of 305 cholecystectomies were performed for biliary colic (73%), choledocholithiasis (9%), cholecystitis (8.4%) and pancreatitis (6.4%). A total of 12.7% had cholangiographic evidence of PBM and 11.9% possessed gallbladder mucosal changes. Overall, 7.7% had increased biliary amylase, which was associated with significantly higher rates of gallbladder intestinal metaplasia (33% versus 8.6%; P = 0.012). Elevated biliary amylase was also higher in patients with prior pancreatitis ( P = 0.02) or choledocholithiasis ( P < 0.01). The presence of PBM did not predict for the presence of PBR. Conclusion: PBR is associated with an increased frequency of gallbladder mucosal metaplasia, irrespective of the presence of PBM. Objectively identified reflux represents an additional indication for cholecystectomy but the long‐term consequences for extra‐hepatic biliary malignancy remain unknown and warrant further investigation. Methods of objectively identifying PBR pre‐operatively require further investigation.